Pemberdayaan Ibu Rumah Tangga melalui KWT dalam Meningkatkan Kesejahteraan Keluarga - Khoirunnisa, Dinda Citra; Sumpena, Deden; Dewi, Ratna (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
This study aims to find out about the empowerment program carried out by the Malati Asih Farmer Women’s Group, the empowerment process, and the results obtained from the Malati Asih Women’s Farmer’s Group in Cinanjung Tanjungsari Village, Sumedang Regency. The method used in this study used qualitative and descriptive research methods with data collection through interviews, observation, and documentation studies. The results of research conducted at KWT Malati Asih include: There are two empowerment programs implemented, namely the KRPL program which focuses on managing agriculture in the yard of the house, and the Savings and Loans Cooperative which aims to provide capital for member businesses. The empowerment process is carried out in four stages, namely identifying and assessing regional potential, problems, and opportunities; preparing group activity plans; implementing the activity/implementation plan; and monitoring/supervision. the presence of housewives’ products; add insight into the world of agriculture; have skills and can help the family economy and family welfare.